Kontektualisasi Hadis: Menyikapi Fenomena Prank di Media Sosial - Reza Pahlevi Dalimunthe; Nadea Siti Saadah (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
As Muslims, we should know what jokes are to stay in the corridor of goodness and not deviate from the path of evil. This research aims to discuss a problem that is rife in social media today, namely pranks. The research methodology used is a qualitative type through library research. The result and discussion of this research are the prank phenomenon mushroomed in society is one of several things that was prohibited by the Prophet Muhammad. But aside from that, some pranks or jokes are allowed. That is, they don't go overboard. So, among the limitations are that it does not contain lies, does not exaggerate, still includes things of goodness, and does not criticize.